Interpreting Life Values in The Performance of Ramayana Shadow Puppet Setubanda Play - Marajaya, I Made (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
Ramayana Shadow Puppet Performance is a type of Balinese shadow puppet from the Ramayana Epic, and its position still exists in society today. The Ramayana Shadow Puppet Performance's main characters are Rama a symbol of good and Ravana a symbol of evil. The characters consist of humans, monkeys (ore), and giants. This performance of Ramayana story is famous for its characteristic